Training for Gold - Chervitz, H. (Swimming Technique, 2004)
Yana Klochkova, the world`s most dominant female individual medley swimmer, is intent on defending her Olympic titles in both IMs at Athens this summer. For the past 15 years, Klochkova has been guided by the steady hand of veteran Ukrainian coach, Nina Kozuch, at the Dynamo Swim Club in Kharkov. A swim coach for more than 40 years, Kozuch has coached several other world-class swimmers besides Klochkova. Now, ten other swimmers, mostly 13-year-olds, train daily under her motherly-but-no-nonsense guidance. The coach speaks about: - What Makes Yana Swim? - Yana's 2004 Training Plan , - Expectations and - the Future.